Developing The Salt Centre of Excellence as a Unique Selling Proposition University of Trunojoyo Madura - Makhfud Efendy; Wiwit Sri Werdi Pratiwi; Aries Dwi Siswanto (Juvenil, 2023)
AbstractAs one of the most enormous salt globally, Indonesia consumes more than 3 million tonnes of salt annually, mainly imported from several countries. However, Indonesia is the second-longest equatorial coastline in the world, with abundant salt resources from the sea. Developing a salt industry development centre on Madura Island is a crucial solution to eradicate Indonesia's label as a salt imported dependent state. Madura Island has large salt production and is labelled a salt island. Being a centre of academics on Madura Island, the University of Trunojoyo Madura is qualified as a salt centre of Excellence due to having met thorough research and development, sourcing absorptive and disseminating capacity guidelines. Research and academic activities in the salt field, such as attending scientific seminars and conferences, participating in workshops and other centers of excellence collaboration, have been done in a decade as academic Excellence. Several industries have produced and utilized the commercialization of research products like fortified salt, rich mineral salt, and solus per aqua (SPA) salt. University also develops collaborative research, advisory and informal knowledge exchange between the university and industry. To implement this program's success, the university develops information systems technology to manage the Centre of excellent performances. Finally, based upon the work done on several guidelines, the university's positive impact on research, industrial corporation, and product dissemination has increased dramatically over the years. Keywords: salt centre of excellent, unique selling proposition, University of Trunojoyo Madura